Novel evidence for within-species leaf economics spectrum at multiple spatial scales - Hu, Yu-Kun; Pan, Xu; Liu, Guo-Fang; Li, Wen-Bing; Dai, Wen-Hong; Tang, Shuang-Li; Zhang, Ya-Lin; Xiao, Tao; Chen, Ling-Yun; Xiong, Wei; Zhou, Meng-Yao; Song, Yao-Bin; et al. (Frontiers in Plant Science, 2015)
Leaf economics spectrum (LES), characterizing covariation among a suite of leaf traits relevant to carbon and nutrient economics, has been examined largely among species but hardly within species. In addition, very little attempt has been made to examine whether the existence of LES depends on spatial scales. To address these questions, we quantified the variation and covariation of four leaf economic traits (specific leaf area, leaf dry matter content, leaf nitrogen and phosphorus contents) in a cosmopolitan wetland species (Phragmites australis) at three spatial (inter-regional, regional and site) scales across most of the species range in China. The species expressed large intraspecific variation in the leaf economic traits at all of the three spatial scales. It also showed strong covariation among the four leaf economic traits across the species range. The coordination among leaf economic traits resulted in LES at all three scales and the environmental variables determining variation in leaf economic traits were different among the spatial scales. Our results provide novel evidence for within-species LES at multiple spatial scales, indicating that resource trade-off could also constrain intraspecific trait variation mainly driven by climatic and/or edaphic differences.